Complaint Strategies Found on Instagram Account @Indihome From Indonesia and @Tmobile From USA: Cross-Cultural Pragmatics - Kharis Marpurdianto (JL3T (Journal of Linguistics, Literature and Language Teaching), 2022)
Social media is one of the ways that are not only for having a new friend but also a business place. Companies might consider to promote their products especially on Instagram. However, the company must be ready to accept critics and complaints from the customers. This study aims to analyze complaint strategies used by Indonesian and American customers on Instagram @indihome and @tmobile. The qualitative method is used in this study because this research produces descriptive data such as speech, writing, and the behavior of each people, which has been observed with the totals of 250 netizen’s comments in the comment column of those two Instagram accounts. The result shows differences and similarities between Indonesian and American netizens expressing complaints on the Instagram accounts of @indihome and @tmobile. The similarities between the Indonesian and American netizens are using the linguistics features to express complaints such as abbreviation, capitalization, and informal language. While the differences are that American netizen never uses code-switching to express complaint because this country was included in the monolingual country. Thus, the Indonesian netizen tends to use code-switching to express their complaint because this country is included in the multilingualism-based country.